Design and construction of a simple energy storage themed game as a teaching aid in schools. (May 2020) - Yan, Maximilian; Entwistle, Jake; Homan, Samuel
Abstract: The need to reduce the consumption of fossil fuels stems the current issues regarding climate change. As sources of renewables are considered as a method of obtaining clean energy in the long term, its intermittency highlights the importance of energy storage technologies. Our energy landscape will continue to change rapidly in the coming decades, so it is important to inspire younger generations and increase awareness in the current generation about how energy storage technologies will help shape our energy landscape. This game, built from simple electronic components, acrylic and 3D printed models, aims to demonstrate the role of energy storage in our current energy infrastructure, and the inform players about issues surrounding the topic.